Bridging the educational gap in terms of digital competences between healthcare institutions' demands and professionals' needs - O. Navarro-Martínez; J. Igual-García; V. Traver-Salcedo (BMC, 2023)
Abstract Background Healthcare professionals with insufficient digital competence can be detrimental to patient safety and increase the incidence of errors. In order to guarantee proper care, healthcare organizations should provide opportunities to learn how to use technology, especially for those professionals who have not received training about this topic during their undergraduate studies. Objective This exploratory study aimed to conduct surveys among Spanish healthcare professionals to determine whether their organisations had trained them in the use of healthcare technology and the areas where most emphasis was placed. Methods 1624 Spanish healthcare professionals responded to an ad hoc online survey 7 questions related to the digital skill training offered by the healthcare organisations they work for. Results Nurses were the most widely represented group, making up 58.29% of the total, followed by physicians namely 26.49%. Only 20% of the nurses surveyed had received some training from their institution related to healthcare technology. According to the participants' responses, physicians received significantly more training in this area than nurses. Training related to database searching for research purposes or computer management followed the same trend. Nurses also received less training than physicians in this area. 32% of physicians and nurses paid for their own training if they did not receive any training from institutions. Conclusions Nurses receive less training, on topics such as database searching or management, from the healthcare centres and hospitals where they work. Moreover, they also have fewer research and digital skills. Both of these factors may lead to deficits in their care activities, and have adverse effects on patients. Not to mention fewer opportunities for professional progress.